THE IMPACTS OF BILINGUALISM ON CHILDREN’S LANGUAGE DEVELOPMENT - Alimova Madinabonu Islomjon qizi (American Journals, 2023)
Bilingualism has been shown to have a positive impact on children's language development. Studies have shown that bilingual children generally have a better understanding of grammar and syntax, as well as a broader vocabulary than their monolingual peers. Indeed, learning two languages forces children to constantly switch between different language systems, which can improve their cognitive flexibility and problem-solving skills. Bilingualism can also help children develop better communication skills by learning how to navigate different cultural contexts and communicate with people from diverse backgrounds. In addition, bilingualism can lead to increased cultural awareness and empathy, as children are exposed to different perspectives and ways of thinking. However, it is important to note that the benefits of bilingualism can depend on factors such as the age at which a child begins to learn a second language, the level of exposure to each language, and the quality of education that children receive. It is also important for parents and educators to support bilingual children in maintaining and developing both languages, as they may face social pressure to prioritize one language over another.
Keywords: Bilingualism, Children's development, language learning, multiple languages.